Ultra-High Performance Concrete UHPC : Fundamentals, Design, Examples. - Fehling, Ekkehard (Beton-Kalender series., 2014)
Selected chapters from the German concrete yearbook are now being published in the new English ""Beton-Kalender Series"" for the benefit of an international audience. Since it was founded in 1906, the Ernst & Sohn ""Beton-Kalender"" has been supporting developments in reinforced and prestressed concrete. The aim was to publish a yearbook to reflect progress in ""ferro-concrete"" structures until - as the book''s first editor, Fritz von Emperger (1862-1942), expressed it - the ""tempestuous development"" in this form of construction came to an end. However, the ""Beton-Kalender"" quickly became.